PRINSIP ETIKA POLITIK PEMIMPIN DALAM ISLAM - Farhah Farhah; Achmad Farid (UNIDA Gontor, 2019)
Human relationships with ethics become the main points of concern in everyday life. Eliminating ethics from political life can have implications for Machavellistist political practice. Islamic political ethics has a sacred basis of the revelation of God and the Sunna of the Prophet. Leaders in Islam are said to be khālifah or imâm. The Caliph is the successor of the prophet as a leader who obeys God's command and enforces the law justly. The wide-ranging moral values should be the basis and consideration of political actions and legitimacy. Principles of political ethics of Muslim leaders viewed from the thinking of classical Muslim philosophers. There are five principles of Islamic political ethics that must be owned by a leader as well as a politician as a power holder in a country: (1) Religion as the ethical basis of Muslim leaders; (2) The mandate in power; (3) Fair and wise in law; (4) Smart and competent in their field; and (5) Deliberation and tolerance.